PENGEMBANGAN MODEL LATIHAN SHADOW FIGHT SEBAGAI VARIASI LATIHAN KELINCAHAN PADA KARATE KATEGORI KUMITE USIA 14-15 TAHUN - Muhammad Bintang Hidayatullah; Raymond Ivano Avandi; Muhamad Fauzi Antoni; Dewangga Yudhistira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Agility is one of the most important biomotor components underpinning the performance of kumite karate athletes, as it is closely associated with rapid changes of direction, attacking, defending, and decision-making during competition. However, the availability of systematic training models specifically designed to meet the demands of kumite remains limited. This study aimed to develop a shadow fight training model in the form of a book-based module as an alternative training programme to improve the agility of kumite karate athletes aged 14–15 years. This research employed a Research and Development (R&D) approach by adapting the Four-D model, consisting of the define, design, and develop stages. The developed product was validated by subject-matter and media experts before undergoing small-scale and large-scale practicality testing involving karate coaches. Data were analysed using Aiken's V coefficient, the Intraclass Correlation Coefficient (ICC), and percentage analysis. The findings demonstrated that the training model achieved high content validity, with Aiken's V values ranging from 0.75 to 0.90. Inter-rater reliability was categorised as excellent, with an Average Measures ICC value of 0.916. Furthermore, the practicality assessment yielded scores of 88.6% in the small-scale trial and 87.7% in the large-scale trial, both classified as highly feasible. Therefore, the book-based shadow fight training model was found to be valid, reliable, practical, and suitable for use as a supporting training medium to enhance the agility of kumite karate athletes aged 14–15 years.